Pengaruh Literasi Keuangan, Aktifitas Galeri Investasi Syariah Dan Pengelolaan Uang Saku Terhadap Minat Mahasiswa Dalam Berinvestasi Saham Syariah Di Pasar Modal - Dimas Dwi Amrico Py; Arsa Arsa; Nurlia Fusfita (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Investing in the Shariah capital market is not only a potential business choice but also an embodiment of the recommended practice of muamalah in Islam, where wealth is used productively to bring benefits to oneself and others. This study found that financial literacy has a significant influence on students' investment interest, with a significance value of 0.000. Financial literacy plays a crucial role in shaping wise financial behavior, where a deeper understanding of finance and investment can help individuals manage their finances better. Additionally, Shariah investment gallery activities also have a significant influence on students' investment interest, with a significance value of 0.012. These activities provide students with a deeper understanding of the mechanisms and principles of the Shariah capital market, thereby increasing their interest in investing. Managing pocket money is also a significant factor in determining students' investment interest, with a significance value of 0.003. Wise management of pocket money allows some students to use part of those funds for investment, subsequently increasing their interest in the Shariah capital market. Simultaneously, the research results show that financial literacy, Shariah investment gallery activities, and pocket money management have a significant influence on students' investment interest, with a significance value for the F-test of 0.000.